PENERAPAN MODEL PEMBELAJARAN EXAMPLES NON EXAMPLES UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS XII.5 DI SMA NEGERI 1 JENEPONTO - Fina Damayanti, Nurul; Bunyamin, Andi; Mustamin; Wahab, Abdul; Raehana, Syarifah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT This study discusses the "application of the Example Non-Example learning method in Islamic Religious Education subjects in class VII.5 SMA Negeri 1 Jeneponto. This study is motivated by the low learning outcomes of students who are still far from the Minimum Completion Criteria (KKM). This study aims to describe the application of the Example Non-Example method in improving student learning outcomes in Islamic Religious Education subjects. The research method used is Classroom Action Research (CAR) by referring to the Jhon Ellio model which consists of two cycles each at the planning, action, observation, and reflection stages. The subjects in this study were students of class VII.5 SMA Negeri 1 Jeneponto with a total of 31 students. Data collection techniques used observation, interviews, tests and documentation. While the data analysis used is quantitative data analysis and qualitative data. The results of the study show that the application of the Example Non-Example learning method significantly improves student learning outcomes. In the pre-cycle stage, the average score was only 61.67 with a mastery percentage of 25.80% (Very Poor category). In Cycle I, the average score increased to 71.80 with a mastery percentage of 51.61% (Poor category). The improvement continued in Cycle II, where the average score reached 84.25 with a mastery percentage of 83.87% (Good category). The implementation of the Examples Non Examples method proved to enhance students’ focus, concentration, active participation, classroom interaction, and appreciation of religious values. Therefore, the Examples Non Examples method is effective in improving both students’ learning outcomes and the quality of the Islamic Religious Education learning process in class VII.5 at SMA Negeri 1 Jeneponto. Keywords: Example Non Examples, Learning Outcomes, Islamic Religious Education